How Stable Are Corporate Capital Structures? - DeANGELO, HARRY; ROLL, RICHARD (Journal of Finance, 2015)
ABSTRACT Leverage cross‐sections more than a few years apart differ markedly, with similarities evaporating as the time between them lengthens. Many firms have high and low leverage at different times, but few keep debt‐to‐assets ratios consistently above 0.500. Capital structure stability is the exception, not the rule, occurs primarily at low leverage, and is virtually always temporary, with many firms abandoning low leverage during the post‐war boom. Industry‐median leverage varies widely over time. Target‐leverage models that place little or no weight on maintaining a particular ratio do a good job replicating the substantial instability of the actual leverage cross‐section.